Coating on surface to transmit electrical current
Patent Information
- Application Number
- JP2023136000
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-08-24
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2043-08-24
AI Technical Summary
Existing coatings for electric vehicle charging contacts face issues with wear behavior, contact resistance, and high costs due to the use of silver alloys, which increase resistance and wear with mating cycles, especially in high-power charging applications.
A coating with multiple layers of different microstructures, including nanocrystalline and coarse-grained silver layers, embedded with graphite particles, is applied using electrodeposition and mechanical impact to enhance wear resistance and reduce thickness, thereby stabilizing contact resistance and reducing costs.
The coating significantly reduces wear during 20,000 to 50,000 mating cycles, allows fast charging without current derating, and lowers costs by minimizing the use of precious metals, while maintaining low contact resistance and preventing black finger/tray effects.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a coating on a surface of a substrate, the coating being specifically designed to transmit electrical current in automotive plug connections, especially terminals for charging batteries in electric vehicles (EVs).
[0002] The present invention also relates to coated charging contacts for use in automobile charging ports and charging guns.
[0003] The invention further relates to an automobile charging connector, in particular comprising a charging port and / or a charging gun, and comprising a coated charging contact, the automobile charging connector being part of an automobile plug connection for charging an EV battery. [Background technology]
[0004] As described further throughout this application, the coating-covered charging contacts in an infrastructure-side vehicle charging connection (typically with a charging gun and typically complementary to an electric vehicle having a charging port side) are part of the present invention since the charging contacts are provided as part of the vehicle charging connection.
[0005] High power charging (HPC) of EV batteries relies on ever increasing currents to reduce charging times, for example for a 100 kWh battery, from 30 minutes to 5 minutes. To transmit currents to charge the traction battery, especially in HPC applications, charging contacts are required that can transmit high currents (e.g., more than 200 A) at high voltages (e.g., more than 100 V, 200 V, or 400 V) with particularly low contact resistance and can withstand many mating cycles (e.g., at least 10,000, 20,000, or 40,000) without a significant increase in contact resistance. Important points are the wear behavior and electrical contact resistance of the charging contacts, which may result in Joule heating and / or current derating.
[0006] Silver (Ag) has been developed as a promising material to be used as a coating for parts made of copper or copper alloys, resulting in good electrical conductivity and wear behavior. Coatings containing silver can be applied using electrodeposition processes. However, silver or predominantly metallic (hard) silver alloys are still subject to wear due to mating cycles, especially after 3000 mating cycles or more. It is known to increase the hardness of the silver coating by alloying it, but this can increase the contact resistance in an undesirable way. It is further known to add graphite (C) particles to the silver alloy to provide an inherent lubrication to the coating. An increase in contact resistance can occur, which is mostly related to the co-deposited organics. Increasing the thickness of the silver coating improves the wear behavior, but unnecessarily increases the cost. Summary of the Invention [Problem to be solved by the invention]
[0007] The object of the present invention is to improve the wear behavior, stabilize the contact resistance at the pure Ag level, and reduce the cost by reducing the coating thickness for forming the coating on the substrate. A further object is to provide a coated charging contact and a coated automotive plug connector / charging port. [Means for solving the problem]
[0008] The solution according to the invention is provided by the subject matter of claims 1, 12, 13 and 15. Preferred embodiments are the subject matter of the dependent claims.
[0009] In particular, a coating on a surface of a substrate, the coating being designed to carry electrical current in an automotive plug connection for charging an EV battery, the coating having layers of different microstructure and performance extending at least substantially parallel to the surface, the coating comprising: at least one layer comprising silver grains of nanocrystalline size, i.e. exhibiting an average size of less than 1000 nanometers (nm), in particular greater than 1, 50 or 300 nanometers, and graphite particles, - at least one coarse layer adjacent to the fine layer and containing mainly or only silver particles having a grain size larger on average than that of the fine layer; A coating is proposed which comprises:
[0010] The layers of different microstructures and performances are particularly limited in thickness, usually less than the entire coating. The same applies particularly with respect to width. Each layer of different microstructures and performances may comprise or be composed of a plurality of particles and / or phases, particularly silver-based, that differ in particular in the arrangement, distribution, shape and / or size of the particles and / or phases, and in particular one or more of said layers may comprise graphite particulates and / or other self-lubricating / self-lubricating particulates, such as PTFE particulates or sulfide-containing particulates.
[0011] Generally, the particulates, i.e., the particulates described herein, such as self-lubricating particulates, graphite particulates, etc., are embedded within and / or between layers. This usually means that the particulates are surrounded by the microstructure and / or layers. This serves to provide a good mechanical and physical connection of the particles to the layers.
[0012] The fine-grained layer may be an intermediate layer and / or an upper layer, which means that the intermediate fine-grained layer is located in particular along the thickness of the coating parallel to the interfacial substrate, i.e. between and / or below the other layers.
[0013] The coatings described herein can be formed by electrodeposition with additional mechanical impacts, which can serve to crush fine particles or apply high energy densities to locally affect the growth / development of the microstructure, allowing both fine and coarse grained layers and an extension at least substantially parallel to the surface to be achieved. The coatings according to the invention can be formed by an electroplating process, preferably barrel plating.
[0014] The "performance" of a layer is related to its mechanical and electrical properties. Typically, different microstructures of any layer result in different performance of said layer. It is therefore desirable for different layers throughout the coating to have such different properties so that a synergistic effect can be realized in combination.
[0015] Even if the nanocrystalline grain size is not present throughout the coating, the nanocrystalline grain size allows a reinforcing effect and / or strength increase of the coating, especially Hall-Petch strengthening. The increase in coating strength correlates with an improved hardness value, so as to improve the wear behavior during friction on the coating at a similar contact resistance. In addition, the graphite allows a self-lubricating effect of the coating, which is useful in electrical plug connections, especially for HPC applications, with high mating cycle requirements that further reduce / limit the wear behavior at low contact resistance. Advantageously, the spread in the mating direction, substantially parallel to the surface, further improves the wear behavior, since in the top view of the coating, a larger area on the surface of the substrate is covered by the coating material, e.g. a layer of high hardness containing nanocrystalline grains. Also, the surface is usually smoother compared to the prior art.
[0016] The present invention eliminates or at least significantly reduces wear during 20,000-50,000 mating cycles at low coating thicknesses compared to prior art coatings containing silver and graphite. This allows fast charging, e.g. within 5 minutes, without current derating and / or durable life of the coated contacts and sockets at low cost. Problematic black finger / tray effects are nearly eliminated by the smooth surface. In short, the present invention therefore provides high sustainability.
[0017] Additionally, the present invention allows for reduced coating thickness compared to the prior art, particularly compared to rack plating, which not only saves application time but also requires less electrolyte for electrodeposition and less precious metal usage, again resulting in cost savings and improved sustainability.
[0018] At least one outermost fine-grained layer comprising silver particles may be provided, the outermost fine-grained layer being in particular located above the remaining layers and / or components of the coating. The wear behavior of the surface of the coating may be locally or at least substantially improved over the entire or substantially the entire surface of the coating.
[0019] The top layer, the outermost fine-grained layer, can exhibit a nanocrystalline grain size, which in particular means that the average grain size is at least less than 1000 nanometers and / or at least more than 1 nanometer, in particular more than 300 nanometers, in order to further improve the wear behavior, in particular when using the new coating during current transmission.
[0020] When the outermost fine grain layer contains particularly randomly dispersed graphite particles, a self-lubricating effect occurs.
[0021] The graphite particles of the outermost fine-grain layer may have a nanoscale size, which particularly means that the average particle size of the graphite particles is at least less than 1000 nanometers and / or at least more than 1 nanometer, in particular less than 750, 500, or 250 nanometers.
[0022] As previously mentioned, the graphite particles are preferably embedded in the fine-grain layer and the outermost fine-grain layer to stabilize the position of the particles relative to the layers.
[0023] In particular the graphite particles of the outermost fine grain layer are spread and / or dispersed at least substantially parallel to and / or along at least one of the surfaces and / or layers.
[0024] In short, the coating can have a smoother surface as well as better wear behavior and better self-lubricating properties, especially when the outermost fine-grained layer at least substantially covers the surface or at least 1%, 5%, 10%, 25%, 50%, 75% or more of the thickness. Based on the idea that the coating can be placed on a substrate having a surface, the outermost fine-grained layer "covers" the surface of the substrate surface location where the outermost region is present. The outermost region does not need to contact the surface of the substrate in order to "cover" said surface in the described sense.
[0025] In particular, the outermost fine grain layer and / or the graphite particles of the fine grain layer can exhibit a nanoscale size, which in particular means that the average particle size is at least less than 1000 nanometers and / or at least more than 1 nanometer, in particular less than 750, 500 or 250 nanometers. The graphite particles are in particular spread and / or distributed at least substantially parallel to at least one of the surfaces and / or fine grain layers. The graphite particles can also spread at least substantially along, in particular parallel to, at least one of the layers and / or the surface. This ensures the presence of a high lubricating effect.
[0026] When the lattice and / or crystal structure of the graphite particles is hexagonal 2H, the self-lubricating effect is improved and the formation of a layer with a substantially parallel extension to the surface during the coating process is facilitated. In addition, when the lattice structure of the silver matrix shows 3C or / and 4H modification, the wear resistance is much improved.
[0027] In particular, the outermost fine-grained layer having at least one or all of the features described above associated with the outermost fine-grained layer can eliminate the black finger / tray effect and provide a smoother surface in contrast to prior art coatings.
[0028] The silver particles of the coarse-grained layer and / or other silver particles with epitaxial growth, in particular the at least substantially silver particles that act as a matrix for the fine-grained layer, <311> : <111> : <220> = 1:0.74:0.46. Alternatively or additionally, the silver particles may exhibit a matrix with 001 and 111 texture that correlates with the 3C and / or 4H modifications described above. Advantageously, layers of different microstructures may be formed in ratios of 1:10 to 1:300.
[0029] At least generally along a portion of the surface, two or more (e.g., three, four, or five) of fine-grained layers, in particular different layers, can be stacked on the surface. "Part" refers in particular to an area of the surface. Thus, the layers can be arranged locally one over the other over the surface relative to the outermost surface of the coating, in particular the layers can be in contact with each other or at least partially separated from each other (e.g., by further layers, further particles, further particulates, and / or the like).
[0030] The coarse-grained layer can exhibit a fine grain size, i.e. an average grain size of at least more than 1 micrometer and less than 1000 micrometers, in particular less than 10 micrometers. Thus, the coarse-grained layer, in particular the multiple coarse-grained layers, can function as a kind of matrix that includes the outermost fine-grained layer and / or the intermediate fine-grained layer. The substantially larger grains can provide, for example, ductility, as opposed to the hardness of the fine-grained layer that is substantially contained in and / or surrounded by the coarse-grained layer.
[0031] Beneath the coarse-grained layer, in particular a (fine-grained) adhesion layer consisting of or comprising Sn and / or Pd and / or Ag and / or Ni and / or Fe and / or Cu flash can be deposited, in particular directly on the substrate. The coarse-grained layer can thus be arranged on the adhesion layer. In particular, the adhesion layer can be arranged beneath the coarse-grained layer located closest to the surface of the substrate and / or beneath at least substantially each of the coarse-grained layers, in particular beneath more than 80% or 90%. The adhesion layer can be part of the coating or of the substrate. The adhesive layer can be advantageous in that it can support the mechanical properties of the coating, in that the coating (or the remainder of the coating relative to the adhesive layer) better connects to the substrate via the adhesive layer, and the risk of delamination of the coating can be reduced.
[0032] Another solution is proposed by a coating on the surface of a substrate, the coating being designed to transmit current in an automotive plug connection for charging an EV battery, in particular with an automotive charging connector comprising a charging port and / or a charging gun, and having layers of different microstructure and performance extending at least substantially parallel to the surface. at least one fine-grained layer comprising silver particles exhibiting a nanocrystalline grain size, i.e. an average grain size of less than 1000 nanometers, in particular more than 1, 50 or 300 nanometers, and self-lubricating microparticles such as graphite and / or nanodiamonds and / or graphene and / or CNTs, lead (Pb), molybdenum (Mo), molybdenum sulfide, silver sulfide, tungsten sulfide, polytetrafluoroethylene (PTFE) or carbonyl fluoride (CFx), the self-lubricating microparticles having a grain size of less than 1000 nanometers, in particular more than 1, 50 or 300 nanometers; - at least one coarse-grained layer adjacent to the fine-grained layer and containing mainly or only silver particles having a grain size larger on average than that of the fine-grained layer; Includes.
[0033] It has been found that the self-lubricating particulates can be replaced or supplemented by graphite particulates. The aforementioned self-lubricating particulates favor a low coefficient of friction of the coating, thereby reducing the wear of the coating during use. The coating can utilize any of the mechanisms and advantages, particularly in the applications described above.
[0034] Further proposed solutions include charging contacts provided for use in automotive plug connections comprising / using automotive charging ports and / or charging guns, which form a charging connection having a substrate of copper or copper alloy or Al or Al alloy with a coating such as one of the coatings mentioned above.
[0035] The contacts may take advantage of any of the features and advantages, among others, and may be used in the applications described above.
[0036] The substrate may comprise at least primarily copper or a copper alloy or Al or an Al alloy, such that good electrical conductivity (compared to silver alloys) is provided at an acceptable cost.
[0037] The substrate may in particular be at least partially rotationally symmetrical and / or flat, in particular such that the connection can be achieved by engagement at the location of a rotated barrel / socket or a flat receptacle, and at least one or both of the two corresponding charging contacts can be connected to a flat or round cable, in particular by bolting and / or welding.
[0038] Furthermore, a charging connector for an automobile is proposed, comprising at least one of the aforementioned charging contacts. The charging connection may comprise a charging port and / or a charging gun, and may be used in particular in an automobile plug connection for charging an EV battery.
[0039] In the case of two or more contacts, the contacts can extend substantially parallel to one another, thus facilitating mating of the corresponding charging contacts and reducing friction of the coating.
[0040] The automotive charging connector may include a housing that holds one or more contacts. The housing may be constructed and / or formed from a polymer / resin. The housing may act as an electrical insulator and / or protector for the contacts and may be further completed / complemented by a shield made of metal.
[0041] The automotive charging connector may include an additional housing and / or additional active and / or passive cooling elements. The additional housing may serve to further protect the charging contacts. The cooling elements may prevent overheating and / or derating.
[0042] The housing and / or the additional housing may cover and / or overlap at least one of the charging contacts in the mating orientation, e.g. to avoid damage to the charging contacts due to unwanted collisions and to increase safety.
[0043] Further details and advantages of the present invention will become apparent from the following description of the prior art and embodiments taken in conjunction with the drawings. [Brief description of the drawings]
[0044] [Figure 1A] FIG. 1 is a cross-sectional view of a coating under SEM analysis according to the prior art. [Figure 1B] FIG. 1 is a cross-sectional view of a coating in EBSD analysis according to the prior art. [Figure 2A] FIG. 2 is a cross-sectional view of a coating under SEM analysis according to the present invention. [Figure 2B] FIG. 1 is a cross-sectional view of a coating in EBSD analysis according to the present invention. [Figure 3A] FIG. 3A: General view of FIB lamellae of a coating according to the present invention with SEM analysis. [Figure 3B] FIG. 3B shows an area including fine and coarse grain layers of the FIB lamella of the coating by SEM analysis according to the present invention. [Figure 3C] FIG. 3C shows a region including the outermost fine-grained layer of the FIB lamella of the coating by SEM analysis according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0045] FIG. 1A shows a coating 1 on a surface 101 of a substrate 100 according to the prior art. The prior art coating 1 can be formed using electrodeposition, in particular a rack plating process. The coating 1 is designed to carry electrical current in an automotive plug connection for charging an EV battery. The microstructure of the prior art coating 1 mainly comprises two layers 10, 20 directly overlying one another, one of which is an outermost layer 10 exhibiting randomly dispersed silver particles 11 and embedded graphite particles 12. The graphite particles 12 are randomly oriented within the layer 10 and / or coating 1.
[0046] The other layer 20 in Fig. 1A is an adhesive layer adjacent to the substrate 100 and in direct contact with the outermost layer 10. The fine-grained layer 20 acts as an adhesive layer and is composed of silver particles 21 and / or nickel particles and / or Cu particles. The two layers 10, 20 extend along and substantially parallel to the substrate interface 101.
[0047] In this prior art example, as well as in combination with any coating 1 of the present invention, a Cu flash can be placed under layer 20 and above substrate interface 101 .
[0048] It can be seen that the graphite particles 12 reach the surface of the outermost fine-grained layer 10, which may cause the surface of the coating 1 to not close and the black finger / tray effect during handling and assembly. The prior art coating 1 is rough and "not closed".
[0049] 1B shows the prior art coating 1 in an EBSD analysis image, where the colors of the original microscope image have been converted to grayscale. Despite the lack of color, it can be seen that the coating in the outermost layer 10 mainly comprises a plurality of microcrystalline silver particles 11 with sizes of more than 0.5 to 10 micrometers, and graphite particles 12.
[0050] The fine-grained layer 20 just below the outermost layer 10 and just above and extending along the substrate interface 101 exhibits the size of nanocrystalline silver particles 21, ie, having an average particle size of less than 1 or 0.5 micrometers.
[0051] In other words, the prior art is composed of an outermost layer 10 and a fine-grained adhesive layer 20. The outermost layer 10 exhibits microcrystalline particles (silver particles 11) and graphite particles 12, and is located directly above a fine-grained layer 20. The fine-grained layer 20 is composed of nanocrystalline silver particles 21. The fine-grained layer 20 does not have any graphite particles embedded / co-deposited therein (hence it does not need to be referenced).
[0052] 2A, 2B show a coating 1 on a surface 101 of a substrate 100, the coating 1 being designed to carry electrical current in an automotive plug connection for charging an EV battery. The coating 1 has layers 10, 20, 30 of different microstructure and performance extending substantially parallel to the surface 101. The coating 1 can be formed using electrodeposition by mechanical impact, which can serve to break up the graphite particulates 12, 22, 32 during the electrodeposition process.
[0053] Compared to the prior art, additional layers, preferably deposited directly on the substrate, such as an adhesion layer and / or a Cu flash, may also be provided.
[0054] 2A, 2B, there is at least one outermost fine-grained layer 10, at least partially comprising silver particles 11 exhibiting a nanocrystalline grain size with an average grain size of less than 1000 nanometers and more than 300 nanometers, which further comprises embedded graphite particles 12. The graphite particles 12 have a nanoscale size, such as an average size of at least less than 1000 nanometers, in particular less than 250 nanometers. The graphite particles 12 extend at least substantially along the layer 10 and the surface 101.
[0055] The coating 1 comprises several intermediate fine-grained layers 20, which comprise silver particles 21 exhibiting a nanocrystalline grain size, i.e. an average grain size of less than 1000 nanometers and more than 300 nanometers, and embedded graphite particles 22, all of which are oriented parallel to the surface 101 of the substrate 100. The graphite particles 22 have a nanoscale size, such as an average size of at least less than 1000 nanometers, in particular less than 250 nanometers. The graphite particles 22 extend at least substantially along the layers 20 and the surface 101.
[0056] Furthermore, the coating 1 of Fig. 2A, Fig. 2B comprises several coarse-grained regions and / or coarse-grained layers 30, which are located adjacent to at least one of the other layers 10, 20 and mainly comprise silver particles 31 (generally silver particles 31 between the presence of several embedded graphite particles 32) that, on average, here exhibit a grain size at least one order of magnitude larger than the grain size of the fine-grained layer 20 and / or the outermost fine-grained layer 10. The silver particles 31 of the coarse-grained layer 30 act as a matrix embedding the intermediate fine-grained layer 20, followed by the outermost fine-grained layer 10, 20, which has a higher hardness and lower ductility than the coarse silver particles 31. It is noted that Fig. 2A shows a measurement artifact A, which is discerned through a blurred boundary.
[0057] In principle, the graphite particles 12, 22 and 32 may be the same or at least similar graphite particles, in particular with respect to crystal structure. However, the graphite particles 12, 22, 32 may also be graphite particles of different sizes.
[0058] Here, graphite particle 12 corresponds to the outermost fine-grained layer 10, graphite particle 22 corresponds to the fine-grained layer 20, and graphite particle 32 corresponds to the coarse-grained layer 30. Thus, if layers 10, 20, 30 cannot be clearly distinguished due to process uncertainties from known coating processes, the correspondence of individual graphite particles 12, 22, 32 may differ. Similarly, substantially the same applies with respect to silver particles 11, 21, 31, where silver particles 11, 21 correspond to fine-grained layer 10 or fine-grained layer 20, respectively, and silver particles such as 30 belong to coarse-grained layer 30, respectively, but only with layers 10, 20, 30 not clearly distinguishable, the problems mentioned above arise.
[0059] 2A and 2B, the outermost fine-grained layer 10 covers the entire surface with different thicknesses, the thicker parts have an area ratio of at least 10%, and the cross-sections shown are evaluated only for this area ratio value. The area ratio with a larger thickness of the fine-grained layer may be different, particularly larger, at other positions.
[0060] The crystal structure of the graphite particles 12, 22, 32 is hexagonal 2H in all cases (i.e., in the outermost fine-grained layer 10, the intermediate fine-grained layer 20, and the coarse-grained layer 30). Moreover, for example, two of the layers 30, 32 are stacked on the substrate interface 101. The coarse-grained layer 30 exhibits a microcrystalline grain size, i.e., an average size of the silver particles 31 at least above 1 micrometer and below 1000 micrometers, here below 5 micrometers.
[0061] It is clear that the coating 1 according to the present invention (FIGS. 2A, 2B) differs in size, distribution and spread of the graphite particles 12, 22, 32 compared to the coating 1 according to the prior art (FIGS. 1A, 1B). According to the present invention, the graphite particles 12, 22, 32 spread mainly substantially parallel to the surface 101 of the substrate 100. According to the present invention, the size of the silver particles 11, 21 in the outermost fine-grain layer 10 and the fine-grain layer 20 is smaller on average compared to the prior art of FIGS. 1A, 1B. The entire silver particles 11, 21, 31 are quite layered (FIGS. 2A, 2B) in contrast to the randomly spread / grown epitaxial silver particles 11, 21 in the prior art (FIGS. 1A, 1B). According to the invention, the content of graphite particles 12, 22, 32 is different (in particular smaller) and the surface roughness values, e.g. Ra or Rz values, are smaller (the surface of the coating 1 is smoother) compared to the prior art.
[0062] Figures 3A-3C show a cross-section of the coating as seen in a FIB cut SEM of a charging contact for use in an automotive plug connection, having a substrate 100 with a coating 1 according to the invention. The coating 1 has layers 10, 20, 30 of different microstructures that run substantially parallel to a surface 101 of the substrate 100. The surface / interface 101 runs substantially parallel to the bottom or top edge of the substrate 100, which is not shown in Figures 3A-3C.
[0063] As best seen in Figures 3A and 3B, there is a fine-grained layer 20 including graphite particles 22 exhibiting a nanoscale size and silver particles 21 exhibiting a nanocrystalline grain size, adjacent to which there is a coarse-grained layer 30 including only silver particles 31 (again, as in Figures 2A and 2B, silver particles 31 between several graphite particles 32), which exhibit a size of the silver particles 31 on average larger than that of the fine-grained layer 20, in particular a microcrystalline grain size (grain size > 1 μm). In addition, there is an outermost fine-grained layer 10 including silver particles 11 exhibiting a nanocrystalline grain size (in particular 300 nm < grain size < 1000 nm) and graphite particles 12 exhibiting a nanoscale size (in particular 1 nm < size < 250 nm). Here, the outermost fine-grained layer 10 covers the coating at least substantially with an area ratio of more than 75%, in particular at least substantially completely.
[0064] The crystal structure of the graphite particles 12, 22, 32 is in particular hexagonal 2H.
[0065] Generally, at least two of the layers 10 , 20 , 30 are stacked on the surface 101 .
[0066] The coating 1 is applied to a substrate 100 made of copper or a copper alloy, Al or an Al alloy, and the coating 1 and the substrate 100 at least substantially form a charging contact, the contact being at least partially rotationally symmetric or flat along a horizontal axis (not shown) below the surface 101.
[0067] An automotive plug connection with charging contacts is not shown, but the connection can have a housing which holds the contacts and / or is made of a polymer / resin, with or without a shield, in particular made of metal, and in special cases has additional mechanisms for cooling the connection.
[0068] In other words, according to the present invention, in particular according to FIGS. 2A, 2B and / or 3A-3C: There may be harder nanocrystalline intermediate layers (outermost fine-grained layer 10 and fine-grained layer 20) at least partially surrounded by silver grains 31 (of coarse-grained layer 30) that notably exhibit a fine-crystalline microstructure; There may be a nanocrystalline boundary hardened top layer (outermost fine grain layer 10) and / or fine grain layer 20, which reduces wear, particularly including embedded graphite particles 12, 22; There may be precisely distributed (small) dispersoid particles (graphite particles 12, 22 in the outermost fine-grain layer 10 or fine-grain layer 20, respectively) that reduce wear, There may be some precisely distributed (small) dispersoid particles (graphite particles 32 of the coarse-grained layer 30) that reduce wear, but this effect may be less than that of the graphite particles 12, 22 of the outermost fine-grained layer 10 or fine-grained layer 20, respectively; There may be a smooth and / or closed surface of the coating 1 (especially the outermost fine-grained layer 10) with embedded graphite particles 12, 22, 32 (especially the graphite particles 12 of the outermost fine-grained layer 10) to avoid the black finger / tray effect, There may be a spreading and dispersion of certain particles with respect to the surface 101 of the substrate 100, substantially parallel to the surface 101; The coarse-grained layer 30 may have and / or surround graphite particles 32, particularly fewer graphite particles 32 than the graphite particles 12 and / or 22 of the other layers 10, 20; and / or The coating 1 may be composed of a layered microstructure, rather than being entirely composed of a layered combination of the outermost fine-grained layer 10, the fine-grained layer 20 and the coarse-grained layer 30, in which locally such layers 10, 20, 30 are distinguished between and / or surrounded by the entire silver particles 11, 21, 31, and graphite particles 12, 22, 32 may be present between the silver particles 11, 21, 31, especially also between the coarse silver particles 31 of the coarse-grained layer 30, and / or surrounded by the silver particles 11, 21, 31. [Explanation of symbols]
[0069] 1 Coating 10 Outermost fine grain layer 11 Silver particles, phase 12 Graphite particles 20. Medium-fine layer 21 Silver particles, phase 22 Graphite particles 23 Particulates, e.g. PTFE and / or molybdenum sulfide 30 Coarse grain layer 31 Silver particles, phase 32 Graphite particles 100 Base material 101 Surface of the substrate A. Artifact
Claims
1. A coating (1) on a surface (101) of a substrate (100), said coating (1) being designed to transmit electrical current in an automotive plug connection for charging an EV battery, said coating (1) having layers of different microstructure and performance extending parallel to said surface (101), The layers of different microstructure and performance include: at least one intermediate fine-grain layer (20) comprising silver particles (21) of nanocrystalline size, i.e. exhibiting an average size of less than 1000 nanometers and more than 300 nanometers, and graphite particles (22); - at least one coarse-grained layer (30) located adjacent to said fine-grained layer (20) and comprising silver particles (31) exhibiting a size on average larger than the size in said fine-grained layer (20).
2. 2. The coating (1) according to claim 1, characterized in that the coarse-grained layer (30) comprises only the silver particles (31).
3. A coating (1) as described in claim 1, characterized in that the layers of different microstructure and performance further comprise at least one outermost fine-grained layer (10) comprising silver particles (11).
4. 4. Coating (1) according to claim 3, characterized in that the silver particles (11) contained in the outermost fine-grained layer (10) exhibit a nanocrystalline grain size, i.e. an average grain size of less than 1000 nanometers.
5. 5. Coating (1) according to claim 3 or 4, characterized in that the silver particles (11) contained in the outermost fine-grained layer (10) exhibit a nanocrystalline grain size, i.e. an average grain size of more than 300 nanometers.
6. The coating (1) according to claim 3, characterized in that the outermost fine-grained layer (10) comprises graphite particles (12).
7. The coating (1) according to claim 3, characterized in that the outermost fine-grained layer (10) covers the surface (101) with an area ratio of 10% or more.
8. 2. The coating (1) according to claim 1, characterized in that the graphite particles (22) in the fine-grain layer have a nanoscale size, i.e. an average size of less than 1000 nanometers.
9. 9. Coating (1) according to claim 1 or 8, characterized in that the graphite particles (22) in the fine-grain layer have a nanoscale size, i.e. an average size of less than 250 nanometers.
10. The coating (1) described in claim 6, characterized in that the graphite particles (12) in the fine-grain layer have a nanoscale size, i.e. an average size of less than 1000 nanometers.
11. The coating (1) described in claim 6, characterized in that the graphite particles (12) in the fine-grain layer have a nanoscale size, i.e. an average size of less than 250 nanometers.
12. 7. Coating (1) according to claim 1 or 6, characterized in that the graphite particles (12, 22) extend along the layer (10, 20) and / or parallel to the surface (101).
13. 7. Coating (1) according to claim 1 or 6, characterized in that the crystalline structure of the graphite particles (12, 22) is hexagonal graphite.
14. 4. Coating (1) according to claim 3, characterized in that along a portion of said surface (101), two of said layers (10, 20, 30) are stacked on said surface (101).
15. 2. The coating (1) according to claim 1, characterized in that the silver particles (31) contained in the coarse-grained layer (30) exhibit a microcrystalline grain size, i.e. an average grain size of more than 1 micrometer and less than 1000 micrometers.
16. 16. Coating (1) according to claim 1 or 15, characterized in that the silver particles (31) contained in the coarse-grained layer (30) exhibit a microcrystalline grain size, i.e. an average grain size of less than 5 micrometers.
17. 2. The coating (1) according to claim 1, characterized in that an adhesion layer consisting of Ag, Ni, Pd, Fe, Sn and / or Cu flash is deposited directly on the surface (101) of the substrate (100) beneath the coarse-grained layer (30).
18. 18. The coating (1) according to claim 17, characterized in that the coarse-grained layer (30) is located closest to the surface (101) of the layers of different microstructure and performance.
19. A coating (1) on a surface (101) of a substrate (100), said coating (1) being designed to transmit electrical current in an automotive plug connection for charging an EV battery, said coating (1) having layers of different microstructure and performance extending parallel to said surface (101), The layers of different microstructure and performance include: at least one fine-grained layer (20) comprising silver particles (21) of nanocrystalline size, i.e. exhibiting an average size of less than 1000 nanometers and more than 300 nanometers, and self-lubricating particles (23) comprising at least one of the following particles: nanodiamond, lead (Pb), molybdenum (Mo), molybdenum sulfide, polytetrafluoroethylene (PTFE), carbon nanotubes (CNT), graphene, silver sulfide, tungsten sulfide, carbonyl fluoride (CFx) or graphite particles (22); at least one coarse-grained layer (30) located adjacent to said fine-grained layer (20) and comprising silver particles (31) comprising self-lubricating particulates and exhibiting a grain size on average larger than the grain sizes in said fine-grained layer (20).
20. A coating (1) as described in claim 19, characterized in that the self-lubricating microparticles (23) contained in the fine-grain layer (20) are graphite microparticles (22).
21. A coating (1) as described in claim 19, characterized in that the self-lubricating microparticles contained in the coarse grain layer (30) are graphite microparticles (32).
22. 20. The coating (1) according to claim 19, characterized in that the coarse-grained layer (30) comprises only the silver particles (31).
23. Charging connector, comprising charging contacts for use in an automotive plug connection with a charging port and / or a charging gun, the charging contacts having a substrate (100) provided with a coating (1) according to claim 1.
24. 24. The charging connector according to claim 23, characterized in that the substrate (100) of the charging contact comprises at least copper or a copper alloy, Al or an Al alloy.
25. A charging connector as described in claim 23, characterized in that the substrate (100) of the charging contact is at least partially rotationally symmetric or flat.
26. A charging connector as described in Claim 23, characterized in that the substrate (100) of the charging contact is a stamped or machined product.
27. 24. A charging connection for an automobile comprising a charging port and / or a charging gun for charging an EV battery using at least one charging contact of the charging connector of claim 23.
28. 24. The charging connector of claim 23, wherein a housing holds the contacts, the housing comprising a polymer.
29. 30. The charging connector according to claim 23 or 28, characterized in that an additional housing is directly connected to the connector or to the busbar or to the cable.
30. A charging connector as described in claim 23 or 28, characterized in that an additional active and / or passive cooling element is directly connected to the connector or to the busbar or to the cable.